Tingkat Persepsi Terhadap Pendidikan Karakter dan Pemahaman Seks pada Mahasiswa - Silalahi, Micha; Arpa, Desi; Hasan, Hasan (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2024)
Based on the results of preliminary data observations carried out by the research team on several students, it was found that some did not understand or know about sex. For students, sex is a form of behavior in the form of getting pregnant outside of marriage, kissing, or even just hugging. Sexual intercourse is considered a natural thing but is contrary to character education. Character education is needed to form an understanding of sex among students. Quantitative research with descriptive analysis using survey methods with the principle of item-total correlation. The total research sample consisted of 145 students, 83 Untad students, and 62 Bengkalis stain students through simple random sampling with a significance level of 5%. Based on the results of the validity trial, there were 17 valid items on the independent variable and 8 valid items on the dependent variable. This research questionnaire has gone through a process of validity and reliability stages. Research on perceptions of character education on understanding sex among students is in the low category.